Corn in postcut crops - A. Y. Kishev; N. I. Mamsirov; R. A. Tiev; E. M. Egorova (Новые технологии, 2023)
In agrotechnologies postcut crops of intermediate cultures are placed after harvesting annual grasses for green mass, and stubble crops after harvesting early grain crops. Annual herbs at the April sowing dates reach mowing maturity and are harvested for green mass in the third decade of June – the first decade of July. However, after harvesting the main crop of the crop rotation, there are still about 70–90 days left until the end of the growing season, which is quite enough to obtain a full-fledged harvest in the hay crops, and thereby increase the index of arable land use [1; 6]. In this regard in 2020–2022 in the foothill zone of the Kabardino-Balkarian Republic (the Baksansky district), the scientific research was carried out on the irrigated Ciscaucasian chernozems (according to B.A. Dospekhov “Methodology of field experience”) in order to study the elements of improving the technology of growing corn in hay crops, providing a reduction in energy costs and optimization of the main parameters of soil fertility. Recently, agricultural production has been operating in the conditions of a resource deficit and an increasingly complex structure of economic relations and an ever-increasing problem of soil and water conservation. The dominance of economic mechanisms fundamentally changes many generally accepted ideas and approaches in the field of agricultural land use. The overall objective is to maximize crop production per unit of input. As a result of the research, it has been found that the cultivation of corn for grain by cutting, after winter rapeseed by chisel processing to a depth of 28–30 cm and the application of fertilizers at a dose of N120P90, contributes to the stabilization of the agrophysical properties of the soil and the optimization of the energy balance